The Influence of Independent Commissioners, Public Stock Ownership, Profitability Moderate Between the Influence of Independent Commissioners and Profitability Moderate Between the Influence of Public Stock Ownership Regarding the Disclosure of Intellectu - Firmansyah, Firmansyah; Rekno Sulandjari; Leonardo Budi Hasiholan (Jurnal Scientia, 2024)
The purpose of this study is to analyze the influence of independent commissioners and share ownership structure on intellectual capital with profitability as a moderating variable in banking companies listed on the Indonesia Stock Exchange. The population and sample in this study are all banking companies listed on the Stock Exchange during the 2013-2015 period. The sample is part of the object that represents the population. The number of research samples was carried out by purposive sampling, where the total all there were 184 within a period of 5 years. Data collection was done by using purposive sampling on all annual report data of all banking companies. Analysis of the data using Statistical Package for the Social Sciences (SPSS) in this case using Moderated Regression Analysis (MRA) as a comparison of the settlers. The results showed that independent commissioners and share ownership structure had a positive and significant effect on intellectual capital. While profitability as a variable is not able to moderate the relationship between independent commissioners and share ownership structure on intellectual capital.